Research on"true community" concept: Textual analysis based on The German Ideology - Wang, Xuan (International Journal of Social Sciences and Public Administration, 2024)
The German Ideology is an important symbol of the maturity of Marxist philosophy. The idea of "true community" deeply reflects the internal logic and development of this original discourse in The German Ideology. Among them, "realistic individual" is the logical source of constructing "true community", the emergence, development and extinction of division of labor is the realization possibility of constructing "true community", and the free and all-round development of people is the ultimate goal of constructing "true community".